Fabrication and static testing of a high-speed morphing rotor blade - Chaudry, Z.; Kuczek, A.; Zhao, W.; Voleti, S.; Gandhi, F.; Camp, D. (My University, 2022)
High-speed rotorcraft experience regions of reverse flow over the inboard sections of blades. In these regions, because of the reverse flow, the rotor blade experiences high drag, large dynamic pitching moments, and significant vibrations. If the shape of the rotor can be changed, or “morphed” in the inboard section, a number of these adverse effects can be minimized. The shape modification which provides optimum benefit between high-speed forward flight and hover was outlined in an earlier paper presented at The Vertical Flight Society's 76th Annual Forum & Technology Display [1]. This paper further builds upon the work presented at the Vertical Flight Society’s 77th Annual Forum & Technology Display [2] and details the fabrication and demonstration of the full-scale rotor blade section capable of meeting the shape change requirements with adequate stiffness and stability. The fabrication of the sub-components and the final assembly of the morphing rotor blade section, which is full scale in the chordwise direction but limited in the spanwise direction, is described. The demonstrator is equipped with a rotary actuator to morph between the hover and high-speed cruise flight conditions. The morphing composite blade demonstrator meets the shape change goals while preserving stiffness and structural integrity.